Antarctophthirus mawsoni Harrison 1937 ... - Leonardi, Maria Soledad; Palma, Ricardo Luis (Zenodo, 2013)
Antarctophthirus mawsoni Harrison, 1937 Antarctophthirus mawsoni Harrison, 1937: 11, pl. 1, fig. 1. Hopkins 1949: 509; Ferris 1951: 73; Gressitt & Weber 1959: 447; King 1964: 137; Clay & Moreby 1967: 166; Clay & Moreby 1970: 220; Gressitt 1970: 329; Dailey & Brownell 1972: 543; Kim et al. 1975: 547; King 1983: 203; Kim 1988: 108; Durden & Musser 1994a: 7; Durden & Musser 1994b: 141; Barker 1996: 236; King 2005: 234. Type host. Ommatophoca rossii Gray, 1844 —Ross seal. Type locality. King George V Island, Antarctica. Type specimen/s data. Holotype Ƥ (Catalogue number K.64350) in the Australian Museum, Sydney, Australia (Australian Museum 2012). Other hosts. None. Geographic distribution. Antarctica and Southern Oceans. Significant references. Durden & Musser (1994a: 7, synonymy, hosts, distribution); Barker (1996: 236, taxonomy). Remarks. Redescriptions of adults and descriptions of nymphal stages are needed. ... : Published as part of Leonardi, Maria Soledad & Palma, Ricardo Luis, 2013, Review of the systematics, biology and ecology of lice from pinnipeds and river otters (Insecta: Phthiraptera: Anoplura: Echinophthiriidae), pp. 445-466 in Zootaxa 3630 (3) on page 452, DOI: 10.11646/zootaxa.3630.3.3, http://zenodo.org/record/221768 ...